MIPAS Detects Antarctic Stratospheric Belt of NAT PSCs Caused by Mountain Waves - Hoepfner, M.; Larsen, N.; Spang, R.; Luo, B. P.; Ma, J.; Svendsen, S. H.; Eckermann, S. D.; Knudsen, B.; Massoli, P.; Cairo, F.; Stiller, G.; Clarmann, T. V.; et al. (2006)
Space borne infrared limb emission measurements by the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) reveal the formation of a belt of polar stratospheric clouds (PSCs) of nitric acid trihydrate (NAT) particles over Antarctica in mid-June 2003. By mesoscale microphysical simulations we show that this sudden onset of NAT PSCs was caused by heterogeneous nucleation on ice in the cooling phases of large-amplitude stratospheric mountain waves over the Antarctic Peninsula and the Ellsworth Mountains. MIPAS observations of PSCs before this event show no indication of the presence of NAT clouds with volume densities larger than about 0.3 micrometer(exp 3)/cm(exp 3) and radii smaller than 3 micrometers, but are consistent with supercooled droplets of ternary H2SO4/HNO3/H2O solution (STS). Simulations indicate that homogeneous surface nucleation rates have to be reduced by three orders of magnitude to comply with the observations. Published in Atmospheric Chemistry and Physics, v6, p1221-1230, 2006.